SAT0531 Altered Expression Levels of MIR-4520A Associated with Familial Mediterranean Fever (FMF). (9th June 2015) - Latsoudis, H.; Mashreghi, M.-F.; Gruen, J.; Chang, H.-D.; Stuhlmueller, B.; Repa, A.; Gergiannaki, I.; Papakosta, P.; Kabouraki, E.; Kardassis, D.; Haeupl, T.; Radbruch, A.; et al.
Abstract : Background: MicroRNA signature of THP1 cells revealed a 5.9 fold decreased expression of miR-4520a following siRNA-mediated knockdown of MEFV gene that encodes pyrin (1). Objectives: We herein sought to validate the expression levels of miR-4520a in monocytes isolated from peripheral blood mononuclear cells (PBMCs) of FMF patients. Methods: Dual luciferase assay and t-test analyses were used to determine the predicted target of miR-4520a, Rheb, after cloning its 3'UTR region containing miR-4520a recognition element into PGL3-prom vector. The expression levels of pyrin, miR-4520a and its putative target Rheb were validated in monocytes from FMF patients (n=10) and compared with healthy controls (n=8). Patients were off colchicine for two days (attack-free period) and monocytes were isolated from PBMCs. Total RNA together with the respective miRNA enriched fractions were isolated from monocytes and used for mRNA and miR-4520a quantitation by real-time quantitative PCR. Expression levels of mRNAs and miRNA were determined with the 2-ΔΔCt method after normalizing to 18S RNA and RNU6B housekeeping genes, respectively. Protein levels of pyrin and Rheb were detected by western blotting. Results: The relative expression levels of miR-4520a were variable among FMF patients and not significantly different between patients and controls. Stratification of patients group by genotype revealed an intriguing difference in miR-4520a relative expression. Specifically, miR-4520a expression was lower in carriers of M694V variant (combined group of homo- and heterozygotes), whereas the rest of FMF genotypes had higher levels (p<0.05). Subsequent comparison between the M694V-group and healthy controls showed a significant reduction in miR-4520a expression levels (p<0.01). Interestingly, one of the homozygote M694V patients with the highest fold change in miR-4520a expression experienced an FMF-attack while on study. Quantitative real time PCR analysis of the miRNA-enriched fraction of total RNA isolated from FMF patient's monocytes during the attack revealed a surprisingly increased miR-4520a expression (FC=0.85) compared to the attack-free period (FC=5.2). Bioinformatic analyses showed that miR-4520a is predicted to target genes implicated in autophagy through regulation of Rheb/mTOR signaling and of Suppressor of IKBKE (SIKE1). Expression levels of the first target we chose to investigate, Rheb, was confirmed by luciferase reporter gene assay as a direct target of miR-4520a (p<0.01). Validation of pyrin and Rheb mRNA and protein expression levels in monocytes from FMF patients is in progress. Conclusions: These findings provide initial evidence that Rheb is a valid target of miR-4520a and suggest that a dysfunctional pyrin due to M694V variant may be associated with a reduction in miR-4520a expression levels thus contributing to the low basal levels of autophagy shown in FMF patients. References: M. F. Mashreghi, H. Latsoudis, J. Gruen et al. (2014). Ann Rheum Dis 73(Suppl2):344-345. Acknowledgements: Supported by the Hellenic Ministry of Education and Gen. Secret. for Research-Technology (ESPA project/No 898). Disclosure of Interest: None declared